2016
DOI: 10.1186/s12887-016-0553-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled trial comparing laryngeal mask versus endotracheal intubation during neonatal resuscitation---a secondary publication

Abstract: BackgroundThis study aimed to study the feasibility, efficacy and safety of using laryngeal mask (LM) ventilation compared with endotracheal intubation (ETI) during neonatal resuscitation.MethodsNeonates with a heart rate below 60 beats per minute despite 30 s of face mask ventilation were assigned quasi-randomly (odd/even birth date) to LM (n = 36) or ETI (n = 32) ventilation. Differences in first attempt insertion success, insertion time, Apgar score, resuscitation outcome, and adverse effects were compared.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…We included a total of seven randomised controlled trials that met the inclusion criteria ( Figure 1). Five studies (661 infants) compared laryngeal mask airway (LMA) to bag and face mask manual ventilation (BMV) (Feroze 2008;Pejovic 2015;Singh 2005;; Zhu 2011); and three studies (158 infants) compared LMA with endotracheal intubation (Esmail 2002;Feroze 2008;Yang 2016).…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We included a total of seven randomised controlled trials that met the inclusion criteria ( Figure 1). Five studies (661 infants) compared laryngeal mask airway (LMA) to bag and face mask manual ventilation (BMV) (Feroze 2008;Pejovic 2015;Singh 2005;; Zhu 2011); and three studies (158 infants) compared LMA with endotracheal intubation (Esmail 2002;Feroze 2008;Yang 2016).…”
Section: Included Studiesmentioning
confidence: 99%
“…Three studies, which enrolled a total of 158 infants, compared LMA with endotracheal intubation (Esmail 2002;Feroze 2008;Yang 2016).…”
Section: Comparison 2: Laryngeal Mask Airway (Lma) Versus Endotracheamentioning
confidence: 99%
See 1 more Smart Citation
“…The authors highlight that this was seen only in babies with higher Apgar scores (i.e., ≥7), probably related to the presence of airway reflexes so it was suggested that in such a situation, an FM and SIB may have been a safer option. Another study, published by the same group, reported vomiting and mild abdominal distention, which the authors attributed to an improper LMA seal over the glottis, with subsequent leaking into the esophagus [31]. Interestingly, there were no complications reported in the neonatal case series and retrospective cohorts of Paterson et al [20], Gandini and Brimacombe [21], Trevisanuto et al [22], and Zanardo et al [24].…”
Section: Complications Of Lmamentioning
confidence: 93%
“…With these limitations in mind, the study suggests that success with the LMA and ETT may be similar for establishing effective ventilation if attempts with an FM have been unsuccessful. In 2016, Yang et al [31] compared the feasibility, efficacy, and safety of LMA and ETT in the neonatal resuscitation of 68 neonates born at >34 weeks' GA and with a BW >2,000 g, whose heart rate did not increase after 30 s of FM PPV. This was a quasi-randomized trial.…”
Section: Lma (N = 24) Vs Ett (N = 25)mentioning
confidence: 99%